Microcontroller based ratio control for electromechanical dual acting pulley continuously variable transmissions - Budianto, Aries (2014)
Electro-Mechanical Dual Acting Pulley Continuously Variable Transmission (EMDAP CVT) is a transmission operated by electro-mechanical actuated system. It has a potential to reduce energy consumption where power is only needed during changing of CVT ratio and no additional power is needed to maintain the CVT ratio due to self-lock mechanism design feature of the EMDAP CVT. In this research, simulation of an EMDAP CVT model was first performed in order to evaluate controller system performance using MATLAB/Simulink software package. Then, confirmation of the simulation results is made by experimental data that is being measured from EMDAP CVT test rig. In order to obtain adequate performance, basic Proportional Integral Derivative (PID), Proportional Derivative (PD) and Proportional Derivative with Conditional Integral (PDCI) controller schemes were proposed to control EMDAP CVT ratio. Relay feedback and Ziegler-Nichols methods were utilized to tune the PID based controller parameters. From simulation analysis, the basic PID based controller shows a huge overshoot up to 280% and it takes very long settling time up to 65 seconds. However, this controller generates very small steady state error which is around 0.2%. The PD controller shows better performance where there is no overshoot occurred and faster settling time, i.e. 8 seconds, but steady state error is a bit higher, i.e. 3.2%, than the basic PID based controller. The best performance is predicted by PDCI controller where it shows maximum overshoot at 0.2%, 8 seconds in settling time and steady state error at 0.1%. In the experimental work, only PD and PDCI controller schemes are adopted because of their good control performance in the simulation. It is found that performance of the PD and PDCI controllers in the experiments are quite close to those predicted in the simulation. For the PD controller, experimental results show no overshoot, it takes only 4 seconds in settling time and produces steady state error of 10%. As for the PDCI controller, it shows 1% in maximum overshoot, 8 seconds in settling time and steady state error at 1%. This indicates that the PDCI controller is superior than the PD controller in terms of steady state error and this is confirmed by simulation and experimental results.